Model Berpikir Deduktif dalam Memahami Islam - Anisa Rahmawati; Yadira Rizka Aulia; Wahdinah Wahdinah; Surya Sukti (Universitas Serambi Mekkah, 2024)
Epistemology is language, speech, or knowledge, its prerequisites, the basis and responsibility for statements about the knowledge possessed.The basic sources of Bayani's epistemology include basic sources, methods (processes and procedures), approaches, faculties and tools of reason, as well as types of reasoning. Epistemology is the foundation and responsibility for language, conversation, or knowledge, its premises, and statements about the knowledge it has. The basic sources of Bayani epistemology include basic sources, methods (processes and procedures), approaches (apprpach), functions and tools of reason, types of reasoning, criteria for scientific validity, basic principles, support. The term irfan or maqrifat refers to knowledge obtained directly from God (kashf) through spiritual practices (riyadra) carried out on the basis of habu (love) or iradha (strong will)